General Phonological and Morphological Justifications of Homophones (مجلة ديالى للبحوث الانسانية, 2022)
General Phonological and Morphological Justifications of HomophonesThis research presents an analysis of ( 750 ) homophonic sets. It shows  two types of systematic linguistic justifications stand behind the sound sameness and spelling difference of homophony. The phonological justifications are the Sound Spelling Correspondence ( SSC) , Elision ( E ) , and Doubling  Grapheme( DG ), while the morphological justifications includes the Suffix Formation ( SF ) and Contraction ( C ).  The order and percentage of the occurrences of them are SSC ( 48 %), E ( 21.5 % ) , SF (20 %), DG  ( 7.1 % ),  and C  ( 2.3 % )  respectively . SSC  is the dominance justification - the substitution of graphemes which are identical phonologically-  and often occurs with the other justifications as a  participant . E – graphemes are phonologically elided and orthographically present- comes secondly and the DG - orthographical doubled grapheme -  takes the fourth place. Both E and DG make the spelling difference obvious. The SF and C have the third and fifth places respectively, which entail the English learner  to consider these morphological issues seriously. A small group (1.1 % ) includes complex homophonic sets created by the cooperation of more than one justification. Consequently, homophony is not arbitrary phenomenon and certain generalizations are coined which can be useful  to know the odd nature of homophones and predict them systematically .